2021
DOI: 10.36909/jer.v9i2.9073
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of tricept parallel manipulator with particle swarm optimization using performance parameters

Abstract: The parallel manipulators are skilled for their precision manufacturing but need optimized design to get maximum dexterity that will lead towards better industrial production rates. The 3-DOF tricept is chosen to utilize its maximum capabilities for its functionality. Three performance parameters conditioning index, workspace volume, and global conditioning index are used to obtain optimum design variables of tricept mechanism. With a view to compare them in terms of processing effort, particle swarm optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Noteworthy is the comparative analysis of the convergence performance of the genetic algorithm (GA) and the particle swarm optimization (PSO), revealing the superior performance of the PSO algorithm. Farooq et al 31 optimized the Tricept mechanism through genetic algorithms to enhance its performance metrics. In a bid to augment existing research endeavors, this study introduces the Weighted Particle Swarm Optimization (PSO) technique for multi-objective optimization, offering a comparative analysis with previous optimization methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy is the comparative analysis of the convergence performance of the genetic algorithm (GA) and the particle swarm optimization (PSO), revealing the superior performance of the PSO algorithm. Farooq et al 31 optimized the Tricept mechanism through genetic algorithms to enhance its performance metrics. In a bid to augment existing research endeavors, this study introduces the Weighted Particle Swarm Optimization (PSO) technique for multi-objective optimization, offering a comparative analysis with previous optimization methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of GA is that many parameters need to be selected by experiences, such as the operator parameters of crossover rate and mutation rate [34]. Different from the crossover and mutation operating of GA, PSO is easier to be implemented because the search is determined according to its speed [35]. Yun et al [36] found that fitness value of the PSO algorithm is better than that of the GA in the optimization of a 3PUPU parallel mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel manipulators (PMs) have become a research hotspot because of their excellent dynamic performance, simple inverse kinematics, and high stiffness (Yang et al, 2022). Sprint (3PRS) (Chen et al, 2014), Tricept (3UPS-UP) (Farooq et al, 2021), and delta (Wang et al, 2014) robots have been successfully commercialized, and the 3RPS PM is used as a parallel module in the five-axis machining center for blade surface machining (Arabshahi and Novinzadeh, 2015). Comprehensive performance of PMs is crucial for machining precision.…”
Section: Introductionmentioning
confidence: 99%